If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + x = 0.333(12x + 6) Reorder the terms: 2 + 3x + x = 0.333(12x + 6) Combine like terms: 3x + x = 4x 2 + 4x = 0.333(12x + 6) Reorder the terms: 2 + 4x = 0.333(6 + 12x) 2 + 4x = (6 * 0.333 + 12x * 0.333) 2 + 4x = (1.998 + 3.996x) Solving 2 + 4x = 1.998 + 3.996x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.996x' to each side of the equation. 2 + 4x + -3.996x = 1.998 + 3.996x + -3.996x Combine like terms: 4x + -3.996x = 0.004x 2 + 0.004x = 1.998 + 3.996x + -3.996x Combine like terms: 3.996x + -3.996x = 0.000 2 + 0.004x = 1.998 + 0.000 2 + 0.004x = 1.998 Add '-2' to each side of the equation. 2 + -2 + 0.004x = 1.998 + -2 Combine like terms: 2 + -2 = 0 0 + 0.004x = 1.998 + -2 0.004x = 1.998 + -2 Combine like terms: 1.998 + -2 = -0.002 0.004x = -0.002 Divide each side by '0.004'. x = -0.5 Simplifying x = -0.5
| y+y*4=16 | | 169x^2-182x-61=0 | | 3y+7-y=-2y+3-3y+13 | | 5x+3=-7x+11 | | 162=102-x | | 11x-2x^2-4=11x+4 | | 53-v=184 | | 7cos(x)=x+1 | | 8=13y+2 | | 1/X1/3 | | -5m+4=11 | | (X+4)(3-x)(2x-1)=0 | | 1/X11/3 | | 3r/4-2/35/6 | | ln(8-2x)=0 | | 1/x3 | | 170=2x+4y | | -18-64=6(1+3k) | | 6x^2-5x+1=99ft^2 | | X-4-5=-7 | | 3a+2=6a-4 | | 2x-3-2=-5 | | 48+6x+2y=496 | | 3x+12-6x=8-3x-40 | | (2x-1)(3x-1)=99ft^2 | | x^2+(k-5)x-k=0 | | 3=b/17 | | 3a+2=5-2y | | 6x-3-3=0 | | 2x+7x-9x+21x+5x=0 | | u^2-13.4u-32.56=0 | | x+10=5x+23 |